Model Pembelajaran Adaptif: Untuk Meningkatkan Efektifitas Pembelajaran di Era Digital - Rakha Aditya Putra; Wildan Satio Siregar; Gusmaneli Gusmaneli (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This paper aims to improve learner focus in the learning process by using an adaptive learning model. Adaptive learning can be defined as “the process of generating unique learning experiences for each learner based on the personality, interests, and performance of learners in order to achieve goals such as learner academic improvement, learner satisfaction, effective learning processes and so on. As for data collection in this writing using literature review or literature review by taking sources from journals, books and other scientific works. By using this learning model, it will increase the effectiveness of students in the learning process.